Advances in Nanopathology From Vaccines to Food. - Gatti, Antonietta Morena; Montanari, Stefano (Milton : Jenny Stanford Publishing, 2021)
If observed from an objective, epistemological standpoint, medicine is not a science, at least not in its own right. The most important, key feature missing is repeatability, which makes the doctor's job extremely difficult. Doctors are not scientists but are called upon to use the results of scientific research every day. Therefore, they must keep themselves updated, distinguish what is worth extricating from a huge amount of literature and use the data exclusively in the patients' interest. To be effective, medicine must start from a correct, full understanding of problems, but particulate pollution leads to too many wrong diagnoses. This book, written by the discoverers of nanopathology, is the most advanced in the field. It focuses on how natural, occasionally generated, engineered particles interfere with living organisms, food, drugs and the environment. It represents a bridge between environmental pollution and its impact on human/animal/plant health. Also unique is its new bioengineering-interdisciplinary approach to medicine and solving pathologies of unknown aetiology. It is a valuable aid for medical doctors in their diagnoses of pathologies triggered by nanoparticles internalized in the human/animal/plant body. They will find solutions to some hardly understandable symptoms which some patients report.
7.2 Particles from Mother to Foetus -- 7.3 Drugs Administered during Pregnancy -- 7.4 Drugs Immediately after Birth -- 8. The Future -- 8.1 Particle Removal from Blood -- 8.2 Conclusions -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Nanoparticles; Nanotechnology; Pathology; MEDICAL / General; MEDICAL / Occupational & Industrial Medicine; SCIENCE / Nanostructures